Explicitly Teaching Empathy in Social Studies Content to Support a Humanitarian Worldview - Rodriguez, Andrea (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2022)
Empathy is the ability to view, feel, or understand what another person is or has experienced from their perspective or frame of reference. While this is not a new concept, the impact that teaching empathy, specifically in social studies content, has on a student’s worldview may be underestimated. Utilizing empathy-based teaching strategies to learn social studies content can result in a more humanitarian worldview which benefits everyone in society. In a society with such divisive cultural and political issues, mutual understandings are few and far between. If our goal as social studies teachers is for our students to understand how these social issues affect people differently, explicitly teaching them how to use empathy is a critical component.